Interleaved Modified SEPIC Converters with Soft Switching and High Power Factor for LED Lighting Appliance - Hung-Liang Cheng; Chun-An Cheng; Chien-Hsuan Chang; En-Chih Chang; Lain-Chyr Hwang; Yi-Chan Hung (Applied Sciences, 2024)
A novel ac/dc LED driver with power factor correction and soft-switching functions is proposed. The circuit topology mainly consists of two modified single-ended primary inductance converters (SEPIC) with interleaved operation. The first half stage of SEPIC operates like a boost converter and the second half stage operates like a buck–boost converter. Each boost converter is designed to operate in discontinuous current mode (DCM) to function as a power factor corrector (PFC). The two buck–boost converters that share a commonly coupled inductor are designed to operate at near boundary conduction mode (BCM). Without using any active clamping circuit, auxiliary switch or snubber circuit, the active switches can achieve zero-voltage switching on, and all diodes achieve zero-current switching off. First, operation modes in steady state are analyzed, and the mathematical equations for design component parameters are derived. Finally, a prototype circuit of 180 W rated power was built and tested. Experimental results show satisfactory performance of the proposed circuit.